Canadian French Translation and Preliminary Validation of the Conformity to Masculine Norms Inventory: A Pilot Study - Jalila Jbilou; Natasha Levesque; René-Pierre Sonier; Phillip J. Tully; Iza Pinette-Drapeau; Véronique Sonier; Andréanne Charbonneau; Paul S. Greenman; Jean Grenier; Marie-Hélène Chomienne (American Journal of Men's Health, 2021)
Conformity to masculine norms has been linked to poor mental and physical health outcomes. Its valid assessment among subgroups of the population is therefore a crucial step in the investigation of intercultural variability in the enactment of masculinity, as well as its causes, costs, and benefits. The present pilot study aimed to adapt and conduct a preliminary validation of a French version of the Conformity to Masculine Norms Inventory (CMNI-22), a self-report questionnaire designed to assess overall conformity to male gender standards. The French adaptation of the CMNI-22 (CanFr-CMNI-22) was developed using a forward-backward translation process. The data from a sample of 57 Canadian French men (23–81 years old), collected at two time points 2 weeks apart, were then analyzed to investigate the psychometric properties and factor structure of the CanFr-CMNI-22. Findings indicated adequate internal reliability of the global scores and highly satisfactory test–retest reliability. Correlations with the Male Role Norms Inventory-Short Form (MRNI-SF) at both time points also showed strong convergent validity. Overall, the CanFr-CMNI-22 appears to be a reliable and valid instrument to assess conformity to traditional masculine gender norms in French-speaking men from the general population. This study is a key step in a research process aiming to validate the Canadian French version of the CMNI and contributes to enhance inclusive research and clinical care to foster men’s health.